Ataxia with Oculomotor Apraxia Type 4 with PNKP Common “Portuguese” and Novel Mutations in Two Belarusian Families - Rudenskaya, Galina E.; Marakhonov, Andrey V.; Shchagina, Olga A.; Lozier, Ekaterina R.; Dadali, Elena L.; Akimova, Irina A.; Petrova, Nika V.; Konovalov, Fedor A. (Journal of Pediatric Genetics, 2019)
Ataxia with oculomotor apraxia type 4 (AOA4) is a rare autosomal recessive, PNKP-related disorder delineated in 2015 in Portugal. We diagnosed AOA4 by next generation sequencing (NGS) followed by Sanger's sequencing in three boys from two unrelated Belarusian families. In both families, one of the heterozygous PNKP mutations was c.1123G>T, common in Portuguese patients; biallelic mutations, c.1270_1283dup14 and c.1029+2T>C, respectively, were novel. These are the first reported AOA4 Slavic cases and the first with a “Portuguese” PNKP mutation outside Portugal. Distinction in two brothers was microcephaly but their disease was not severe in contrast to PNKP-related “microcephaly, seizures, and developmental delay” and reported cases with features of both phenotypes.
Keywords: ataxia with oculomotor apraxia type 4; microcephaly; mutation frequency